Mechanism of reward for glass recycling activities in Kuantan community based on mpk redemption system - Wan Humaiyah, Wan Mohamad (2013)
This study was conducted within Kuantan municipal council (MPK) and Kuantan community. This system will develop a new concept on rewarding the consumers upon glass recycling program based on MPK redemption system. The aim objective of this study is to develop recycling reward mechanism concept within MPK and consumer. The elements investigated includes identification of the type of reward to be offered by MPK to their consumer, to know which kind of reward selected by customer and to discover consumers’ behavior towards glass bottle recycling. Throughout the study, 30 set of questionnaires are develop as a pilot test survey from 30 Ump students and 200 sets of questionnaires are prepared and respondents from selected area which are Sg. Isap village, Bandar Indera Mahkota, Cenderawasih and Kubang Buaya Village will be the sample of this survey. Feedbacks from the survey shows 100 % of respondent of pilot test and survey are answered the questionnaires. Based on the results, it can be concluded that most of consumers are interested with the rewards offered by MPK. Majority of Kuantan community prefer to choose “landscape reward” Its shows the highest rating voter for this reward which is 33%. Then followed by “car parking ticket”, 29.5% and “zoo night ticket in Taiping Perak”, 25%. The lowest rating voted is “car parking sticker”.